Islamic Mission Hospital, Golmunda, Jaldhaka, Nilphamari - Dhrubaa, Oeshmita (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2022.